1999
DOI: 10.1680/gi.1999.030403
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of strength of fly ash with lime and sodium salts

Abstract: It is often necessary to improve the strength of fly ash to enable its use for many geotechnical applications. Lime in some form or other is normally used as an admixture. Methods are established to determine the optimum lime content for fly ash, as the addition of lime beyond the optimum lime content may not be beneficial or economically viable. This paper examines the use of sodium salts to enhance the effect of lime on fly ash. Based on unconfined compression strength tests on a compacted fly-ash–lime–salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The addition of 1% of any sodium salt changes the nature of the compaction curve. The MDU reduces with a marginal rise in OMC [21]. Figure 4 shows the effect of RHA, CL and sodium salts on compaction characteristics of BC soil.…”
Section: Compaction Characteristics Of Alkali-treated Soil Optimum Rmentioning
confidence: 99%
See 2 more Smart Citations
“…The addition of 1% of any sodium salt changes the nature of the compaction curve. The MDU reduces with a marginal rise in OMC [21]. Figure 4 shows the effect of RHA, CL and sodium salts on compaction characteristics of BC soil.…”
Section: Compaction Characteristics Of Alkali-treated Soil Optimum Rmentioning
confidence: 99%
“…The addition of NaCl to the composite reacts with lime in the presence of water and leads to the formation of sodium calcium silicate. The addition of sodium salts increases the pH of the composite and reacts with high silica content of RHA and BC soil, leading to alkali silicates and aluminates compounds such as C-S-H, C-A-S-H, S-C-A-S-H and S-C-S-H [21]. Thus, compressive strength of the blended composite enhances.…”
Section: Improvement In Strength Of the Rha-stabilized Bc Soil In Thementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, it is important to consider the possible advantages of using additives or additional binders for enhancing the lime stabilisation process in organic clays with a noticeable humic acid content. It was reported in the literature that salt additives, such as sodium chloride (NaCl), can be used as an admixture so that the characteristics of the lime-treated organic clay can be improved (Asghari et al, 2003;Davoudi and Kabir, 2011;Marks and Haliburton, 1999;Modmoltin and Voottipruex, 2009;Murty and Krishna, 2007;Onitsuka et al, 2002Onitsuka et al, , 2003Ramana and Hari Krishna, 2006;Ramesh et al, 1999;Sharma et al, 2008;Stipho, 1989). The salt additives, being more readily soluble in water than lime, provide the required cations that are necessary for cation exchange.…”
Section: Notationmentioning
confidence: 99%
“…In addition, lime and Portland cement are frequently used in practice to improve the properties, specifically strength, of high moisture content soils. Research has also shown that an alkali activator, such as Na2O, can have a positive effect on the compressive strength and microstructural characteristics of fly ash (Guo et al 2010) with a specific study (Ramesh et al 1999) showing sodium salts improving the strength of fly ash-lime mixtures. According to that previous study, a very small amount of lime, when added with a sodium salt, is all that is needed to solidify the fly ash.…”
Section: Introductionmentioning
confidence: 99%